Efek digital marketing terhadap keputusan berkunjung ke obyek wisata dimediasi oleh minat berkunjung - Andini, Rozy Dwi; Nurfarida, Iva Nurdiana; Rusno, Rusno (MBR (Management and Business Review), 2024)
The research aims to investigation the influence of digital marketing on the decision to visit tourist attractions, as well as test the mediating role of visiting intention on the influence of digital marketing on the decision to visit tourist attractions. The research sample was 112 people visiting the paralayang Bukit Waung Pantai Modangan in Malang Regency. Data was collected using a questionnaire, and data was analyzed using path analysis. The results of the analysis reveal that digital marketing influences the decision to visit, apart from that digital marketing also influences the intention in visiting, and the interest in visiting is also proven to influence the decision to visit tourists at the paralayang Bukit Waung Pantai Modangan in Malang Regency. Another finding from this research is that intention in visiting mediates the role of digital marketing on visiting decisions.